The discourse of liberation: Frames used in characterising the gay liberation movement in two South African newspapers - Mongie, Lauren Danger (Stellenbosch Papers in Linguistics Plus, 2015)
This article reports on the quantitative findings of a study that straddles the applied linguistic field of critical discourse analysis and a sociolinguistic field recently referred to as “queer linguistics”. Drawing on a quantitative method of analysis, the study investigates the linguistic framing of LGBT mobilisation in two South African newspapers, City Press and the Mail & Guardian, across a period of almost 30 years. It aims to identify the characteristics of the discourses that topicalise the gay[1] liberation movement in order to investigate the ways in which linguistic means have been used in articulating the need and the right to liberation and how arguments against the gay liberation movement have been framed, reframed and counterframed in South African media. The study’s findings revealed that a number of frames, including ‘liberation’, ‘rights’ and ‘victimisation’, reoccurred in the framing of arguments for the gay liberation movement throughout the data collection period in both corpora, and while City Press primarily used these frames to express anti-gay sentiments, the Mail & Guardian primarily used these frames to express pro-gay sentiments. The findings also revealed that a number of frames, including ‘religion’, ‘morality’ and ‘nature’, reoccurred in the framing of arguments against the gay liberation movement, and again while City Press primarily used these frames to express anti-gay sentiments, the Mail & Guardian primarily used these frames to express pro-gay sentiments. Finally, the findings revealed that a single frame such as “religion” was typically used to express both pro- and anti-gay sentiments, bringing to light the important role that counterframing plays in bringing about social transformation. [1] The word “gay” is used as a hypernym in this article as this is a reflection of the way in which the liberation movement was typically topicalised in the data.